Thresholds and wearout: An overview - Corkindale, David (Cranfield School of Management, 1977)
This report is the third in a series of three on Thresholds and Wearout in Advertising. The first report summarised the literature and pract¬itioners' initial views on the topics: it attempted to clarify the main issues and problems. The second report presented the results of a survey of current practice and opinions carried out by questionnaire on the advertising management of 23 products or services. The survey attempted to further clarify and quantify sane issues and explore some hypotheses on the.causes of different levels of thresholds and wearout. This third report attempts to summarise what we have found out so far. Further, it attempts to: i) describe what should be considered when thinking of threshold and/or wearout in advertising ii) ennumerate the factors that may influence the occurence of threshold or wearout in advertising iii) suggest what advertising situations are most at risk as far as encountering threshold or wearout situations iv) suggest what should be examined/measured/monitored if it is felt that either, or both, are a potential risk v) give guidelines, for different situations, on the levels of threshold and wearout in advertising. The following sections aim to deal with the above tasks.